Orientation of Spondylus valves cemented to the hard-rock substrates (Bivalvia, Upper Cretaceous, Bohemia) - Zitt,J.; Nekvasilova,O. (Journal of the Czech Geological Society, 1994)
Data on orientation of Spondylus sp.encrusting the rocky bottom and boulders in the nearshore facies (upper Cenomanian-lower Turonian, Bohemian Cretaceous Basin) are summarized and compared with those on encrusting bivalve Atreta. While the subhorizontal rocky surfaces bear both Spondylus sp. and Atreta orientated chaotically, on sloping substrates (the dip equal to or exceeding 10°) they are usually orientated preferentially, i.e., umbos of valves are directed to the upper left quadrant (so-called slope orientation). In agreement with Seilacher (1960) we tentatively consider this posture to be advantageous for nutrition and providing other biological functions. Most recently, a modified orientation of Spondylus was found on the overhanging roof of a small cavity, sheltered from the exterior by a clast barrier. The Spondylus valves are here mostly directed to the lower left quadrant by their umbos. It means that, under the local conditions, the posterior margins of valves were turned to the barrier, through which the cavity communicated with the exterior water environment. A fragment of an irregular cluster with partial radial orientation of Spondylus valves was also found on another substrate of the same locality (Skalka near Velim, central Bohemia). Several extra-Bohemian examples of Mesozoic encrusters are discussed.